PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PADA PT TULIP TONATA INDONESIA KABUPATEN TANGERANG - Khaydatur Rasyifah; Budhi Prabowo (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of the work environment and individual characteristics on the performance of PT employees. Tulip Tonata Indonesia, Tangerang Regency, both partially and simultaneously. The method used is a quantitative method. The sampling technique used was saturated sampling with a sample of 70 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that the work environment has a significant effect on employee performance with the regression equation Y= 16.204 + 0.659X1. Hypothesis testing obtained t count > t table or (12,225 > 1,995). Individual characteristics have a significant effect on employee performance with the regression equation Y = 12.596 + 0.762X2. Hypothesis testing obtained t value > t table or (9.843 > 1.995). The work environment and individual characteristics have a significant effect on employee performance with the regression equation Y= 10,981 + 0.462X1+ 0.329X2. Hypothesis testing obtained calculated F value > F table or (93.065 > 3.134). Thus Ho is rejected and H3 is accepted. This means that there is a significant simultaneous influence between the work environment and individual characteristics on employee performance.